RESPON PERTUMBUHAN DAN PRODUKSI BENIH KENIKIR (Cosmos sulphureus Cav.) TERHADAP DOSIS PUPUK NITROGEN DAN JARAK TANAM - Dwi Satria Nugraha; Maria Azizah (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Kenikir (Cosmos sulphureus Cav.) is a potential vegetable to be developed. Its availability of seeds needs to be developed. This research aims to determine the effect of the interaction between nitrogen fertilizer dosage and planting distance on kenikir seed production. This research was carried out from August to December 2022 in Tegalwaru, Mayang, Jember. The research design with factorial randomized block design. The first factor was the dose of nitrogen fertilizer, 60 kgha-1 (N1), 90 kgha-1 (N2), 120 kgha-1 (N3). The second factor was the plant spacing, 50 x 30 cm (T1), 50 cm x 40 cm (T2), 50 x 50 cm (T3). Data were analyzed using Anova and continued with 5% Duncan test. The results showed that nitrogen fertilizer dose of 120 kg/ha and a plant spacing of 50 x 50 cm had an influence on stem diameter with the largest diameter being 7.39 mm. Nitrogen fertilizer dosage and planting distance did not effecting plant growth paramether in plant height, and plant yield parameters of seed production per plant and seed production per hectare. These results indicate that all combinations of N fertilizer doses and planting distances can be applied in seed production with equivalent results.